Electric-field-induced modulation of thermal conductivity in poly(vinylidene fluoride). (April 2021) - Deng, Shichen; Yuan, Jiale; Lin, Yuli; Yu, Xiaoxiang; Ma, Dengke; Huang, Yuwen; Ji, Rencai; Zhang, Guangzu; Yang, Nuo
Abstract: Phonon engineering focuses on heat transport modulation in atomic-scale. Different from reported methods, it is shown that electric field can also modulate heat transport in ferroelectric polymers, poly(vinylidene fluoride), by both simulation and measurement. Interestingly, the thermal conductivities of poly(vinylidene fluoride) array can be enhanced by a factor of 3.25 along the polarization direction by simulation. The thermal conductivities of semi-crystalline poly(vinylidene fluoride) film can be also enhanced by a factor of 1.5 which is shown by both simulation and measurement. The mechanism is analyzed by morphology and phonon properties. It is found that the enhancement arises from the higher inter-chain lattice order, stronger inter-chain interaction, higher phonon group velocity and suppressed phonon scattering. This study offers a new modulation strategy with quick response and without fillers. Graphical Abstract: Poled by electric field, thermal conductivity of poly(vinylidene fluoride) (PVDF) can be increased, which is proved by both simulations and experiments. The study offers a brand new strategy to modulate thermal conductivity. ga1 Highlights: A new strategy to modulate thermal conductivity of polymer with electric field is proposed and proved. Thermal conductivities in poly(vinylidene fluoride) can be modulated without sacrificing other mechanical properties. Modulation with electric field is in situ, flexible control, quick response and low energy consumption. A detailed analysis on the mechanism of thermal conductivity enhancement is presented.